2012
DOI: 10.1021/ac302807u
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Quantification of Peptides and Proteins by Matrix-Assisted Laser Desorption Ionization Mass Spectrometry

Abstract: Even though matrix-assisted laser desorption ionization (MALDI) is a powerful technique for mass spectrometry of peptides and proteins, it is not quite useful for their quantification that is one of the outstanding problems in quantitative proteomics. The main difficulty lies in the poor reproducibility of MALDI spectra. In this work, a simple method to circumvent this problem has been developed. The method is based on a previous observation that the reaction quotient for the matrix-to-peptide proton transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…We observed such direct proportionality over three orders of magnitude in analyte concentrations and proposed to use it as a calibration curve for analyte quantification [16]. 5.…”
Section: Ion Ratiomentioning
confidence: 82%
See 3 more Smart Citations
“…We observed such direct proportionality over three orders of magnitude in analyte concentrations and proposed to use it as a calibration curve for analyte quantification [16]. 5.…”
Section: Ion Ratiomentioning
confidence: 82%
“…Subsequently, when the analyte was a peptide, we found that I(Analyte)/I(Matrix) was comparable to the analyte concentration in a solid sample [16]. The constancy of Q is an indication that an analyte ion may indeed be produced by the reaction in Equation 1 and that the reaction is nearly at equilibrium.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, Prof. Kim and coworkers have recently dedicated themselves towards the better understanding of the MALDI mechanism and the expansion of the MALDI analysis as a quantitative tool. [6][7][8][9] Another notable contribution made in his group was the coupling of UV light with MALDI technique as a photodissociation (PD) tool, [10][11][12] which has made an impact on the ensuing use of UV light in peptide sequencing mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%